An ex-vivo and in-vitro dynamic simulator for surgical and transcatheter mitral valve interventions - Karl, Roger; Romano, Gabriele; Marx, Josephin; Eden, Matthias; Schlegel, Philipp; Stroh, Lubov; Fischer, Samantha; Hehl, Maximilian; Kühle, Reinald; Mohl, Lukas; Karck, Matthias; Frey, Norbert; et al. (International journal of computer assisted radiology and surgery, 2024)
Minimally invasive mitral valve surgery (MIMVS) and transcatheter edge-to-edge repair (TEER) are complex procedures used to treat mitral valve (MV) pathologies, but with limited training opportunities available. To enable training, a realistic hemodynamic environment is needed. In this work we aimed to develop and validate a simulator that enables investigation of MV pathologies and their repair by MIMVS and TEER in a hemodynamic setting.
Online veröffentlicht: 08. Dezember 2023
Gesehen am 22.01.2024